Demanda de biomasa para generación de energía en los diferentes sectores de la provincia de Misiones = Biomass demand for power generation in different sectors of the province of Misiones - Martiarena, Rodolfo; Silva, Fidelina; Alvarenga, Fernando Agustin; Keller, Aldo Esteban; Correa, Miguel Angel; Marastoni, Ariel (Facultad de Ciencias Forestales, Universidad Nacional de Misiones, 2025)
The objective of this work is to quantify the biomass demand in each department of the province of Misiones which is required by the different sectors for power generation. The WISDOM (Woodfuels Integrated Supply/Demand Overview Mapping) methodology was used to analyse the data provided by the referents of the different sectors. The results show that the greatest demand for biomass is observed in the north-central departments of the province and the consumption is mainly given by pulp mills and energy generators. Although in lower quantities, in the south-central departments of the province the higher consumption is given by the yerba mate, tea and coal industries.